Efek mediasi ketakutan menjadi lajang dalam hubungan antara stereotip negatif dan kesejahteraan psikologi perempuan lajang - Nanik, Nanik; Surijah, Edwin Adrianta; Natalya, Lina; Chrisyanti, Mery (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract The number of single women in Indonesia is increasing, but single women in Indonesia are also vulnerable to negative stereotypes. Unpleasant experiences experienced by single women can have a negative impact. This study examines the association between negative stereotypes and psychological well-being and the mediating effect of fear of being single. The study participants were 196 single women aged 25 – 55 years, had completed their high school, and staying in Indonesia. Participants reported their experiences as single such as psychological well-being, happiness, negative stereotypes, fear of being single, dating experience, and desire to marry. Those experiences were measured by Ryff’s psychological well-being scale (α=0,80), Pignotti’s & Abell’s negative stereotyping of single persons scale(α=0,754-0,88) , Spielman’s fear of being scale (α=0,829), conscientiousness of BFI personality scale (α=0,821) and open questionnaire. Linear regression analysis was performed to test the relationship between variables. The results show that negative stereotypes reduce the psychological well-being of single women in Indonesia, and the fear of being single mediates the association between the two variables. Findings of this study indicate the need for social change to replace unfavourable labels received by single women in Indonesia and provide information for improving the psychological well-being of single Indonesian women. Keywords: fear of being single; negative stereotypes; psychological well-being; single women Abstrak Jumlah perempuan lajang di Indonesia semakin meningkat, namun perempuan lajang di Indonesia juga rentan mengalami stereotip negatif. Pengalaman tidak menyenangkan yang dialami perempuan lajang ini dapat membawa dampak negatif. Penelitian ini mengkaji asosiasi antara stereotip negatif dan kesejahteraan psikologis serta efek mediasi dari ketakutan menjadi lajang. Partisipan penelitian adalah 196 perempuan lajang berusia 25 – 55 tahun, berpendidikan minimal setara dengan SMA dan berdomisili di Indonesia yang melaporkan pengalaman sebagai lajang seperti kesejahteraan psikologis, kebahagiaan, stereotip negatif, ketakutan menjadi lajang, pengalaman berpacaran, dan keinginan untuk menikah. Pengalaman partisipan diukur dengan skala kesejahteraan psikologis Ryff (α=0,80), skala stereotip negatif individu lajang Pignotti dan Abell (α=0,754-0,88), skala fear of being single Spielman (α=0,829), skala BFI kepribadian conscientiousness (α=0,821). Analisis regresi linear dilakukan untuk menguji hubungan antar variabel. Hasil menunjukkan stereotip negatif menurunkan kesejahteraan psikologis perempuan lajang di Indonesia dan ketakutan menjadi lajang memediasi asosiasi kedua variabel tersebut. Temuan penelitian ini menunjukkan perlunya perubahan sosial untuk mengganti label buruk yang diterima perempuan lajang di Indonesia serta menjadi informasi bagi peningkatan kesejahteraan psikologis perempuan lajang Indonesia. Kata kunci: ketakutan menjadi lajang; kesejahteraan psikologis; perempuan lajang; stereotip negatif